Comment on "Deciphering calcium-binding behaviors of casein phosphopeptides by experimental approaches and molecular simulation" by M. Luo, J. Xiao, S. Sun, F. Cui, G. Liu, W. Li, Y. Li and Y. Cao, Food Funct., 2020, 11, 5284. Issue 4 (1st February 2023) - Horne, David S.
Abstract : But this system is not as simple as depicted since co-precipitation of all three reagents occurs when CPP is included.